Meeting our standards for educational justice: Doing our best with the evidence. (March 2018) - Joyce, Kathryn E; Cartwright, Nancy
The United States considers educating all students to a threshold of adequate outcomes to be a central goal of educational justice. The No Child Left Behind Act introduced evidence-based policy and accountability protocols to ensure that all students receive an education that enables them to meet adequacy standards. Unfortunately, evidence-based policy has been less effective than expected. This article pinpoints under-examined methodological problems and suggests a more effective way to incorporate educational research findings into local evidence-based policy decisions. It identifies some things educators need to know and do to determine whether available interventions can play the right casual role in their setting to produce desired effects. It examines the value and limits of educational research, especially randomized controlled trials, for this task.